Shifting the Intellectual Authority in Science Classrooms from Teachers to Students: How Novice Teachers Use Tools to Analyze and Advance Practice - Jessica Thompson; Anna Kramer; Lindsay Carlson; Lindsay Holladay; Bethany Sjoberg (Networks: An Online Journal for Teacher Research, 2014)
To meet the immense challenges our society faces in areas such as energy, health, and environmental protection, we, as science teachers and teacher educators, need to invest in the creation of classroom cultures that turn the intellectual heavy lifting over to the students while developing students’ identities as competent learners. Our vision is that classrooms are both intellectually rigorous—accountable to important ideas and practices in the discipline—and uncompromisingly responsive to students’ developing scientific ideas. Problematically, this type of teaching is currently rare in science classrooms (Corcoran & Gerry, 2011; Kane & Staiger, 2012; Pasley, 2002; Roth & Garnier, 2007; Weiss, Banilower, McMahon, & Smith, 2001). Studies of novice teachers indicate that “the use of analogies, the implementation of strategic approaches to questioning, and the elicitation of student understandings remained virtually absent from their dialogue in class” (Hogan, Rabinowitz, & Craven, 2003, p. 243). Creating rigorous and responsive science learning environments that are the norm rather than the exception in the American educational system is thus a grandscale inquiry project that will require decades of collaboration and investigation to generate a shared vision of quality teaching and learning. The first-year teachers who co-authored this paper are leading this charge. They were one of the first cohorts to complete a teacher education program that focused on learning and inquiring into a core set of ambitious science teaching practices—practices that focus students’ intellectual work on complex problems rather than the typical emphases on activities and procedural talk; are adaptive to students’ needs and thinking; and maintain rigorous standards of achievement for everyone, enabling learners of all backgrounds to succeed at high-quality work (Fennema, Franke, Carpenter, & Carey, 1993; Hill, Rowan, & Ball, 2005; Lampert & Graziani,2009; Newmann & Associates, 1996;).